Explorations in psychoanalytic ethnography - Mimica, Jadran (Berghahn Books, 2007)
"Whereas most anthropological research is grounded in social, cultural and biological analysis of the human condition, this volume opens up a different approach: its concerns are the psychic depths of human cultural life-worlds as explored through psycho-analytic practice and/or the psychoanalytically framed ethnographic project. In fact, some contributors here argue that the anthropological interpretation of human existence is not sustainable without psychoanalysis; others take a less extreme radical stance but still maintain that the unconscious matrix of the human psyche and of the intersubjective (social) reality of any given cultural life-world is a vital domain of anthropological and sociological inquiry and understanding."--Jacket